2016
DOI: 10.1016/j.cplett.2016.09.056
|View full text |Cite
|
Sign up to set email alerts
|

A new mathematical modelling using Homotopyperturbation method to solve nonlinear equations in enzymatic glucose fuel cells

Abstract: A new mathematical modelling using Homotopyperturbation method to solve nonlinear equations in enzymatic glucose fuel cells. Chemical physics letters [online], 662, pages 317-326.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…3 shows the dimensionless steady-state concentrations of species C using Eq. (8). From this figure it is observed that concentration of species C decreases when λ increases.…”
Section: Numerical Simulationmentioning
confidence: 68%
See 2 more Smart Citations
“…3 shows the dimensionless steady-state concentrations of species C using Eq. (8). From this figure it is observed that concentration of species C decreases when λ increases.…”
Section: Numerical Simulationmentioning
confidence: 68%
“…After putting the equations (B31) to (B33) in the equation (B28) to (B30) we obtain the equations (6) - (8) in the text.…”
Section: Appendix B: Analytical Solutions Of Non-linear Equations (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling and simulation of these processes allows understanding and optimizing the performance of enzymatic electrodes and consequently of the entire fuel cell. Specifically, the focus involves the mathematical resolution of the corresponding non-linear reaction-diffusion problems [38,50], including reaction and transport kinetics, statistical analysis and metabolic control analysis. Theoretical, numerical and experimental methods for estimating the biofuel cell performance was discussed by various authors.…”
Section: Non-microfluidic Configurationsmentioning
confidence: 99%
“…Over the last two decades, some nonlinear reaction-diffusion equations have been analytically solved by applying the homotopy perturbation method (HPM) [24]. This method, which is a combination of homotopy in topology and classic perturbation techniques, provides a convenient way to obtain approximate solutions for a wide variety of problems arising in different fields, including reaction-diffusion equation involving Michaelis-Menten kinetics [29,39]. However, often accurate analytical solutions obtained by the HPM are not expressed in the closed form and the accuracy of the constructed closedforms of analytical expressions of the substrate concentration is not satisfactory [37].…”
Section: Nonlinear Steady-state Solutionmentioning
confidence: 99%